Penerapan sistem Informasi Pembayaran Uang Bantuan Pengembangan Pendidikan (BPP) Untuk Meningkatkan Efisiensi dan Akurasi Tata Kelola Keuangan di SMA Negeri 5 Kupang - Bhia, Anastasia Yuniarsih Kartika; Boru, Meiton; Doven, Margareta Jeane; Lehot, Fransisco Ronaldo (Bakti Cendana, 2024)
The education management information system (MIS) must support educational activities. Both are interrelated and need each other. Payment of Educational Development Assistance (BPP) at SMA Negeri 5 Kupang is currently still done manually. This makes it difficult for officers to manage data related to the BPP payment process. Officers must carry out several recording processes in each payment transaction. The purpose of this community service activity is to improve the efficiency and accuracy of BPP payment management at SMA Negeri 5 Kupang. The implementation of this community service activity is divided into several stages, namely needs analysis (observation, interviews and data exploration on the internet), system design (design, coding and testing), implementation and training. This Community Service Activity produces a website-based payment information system that has three menus, namely the admin login menu, student login and payment. The system created can manage financial data and produce reports quickly and accurately and increase transparency and accountability in BPP management. The results of the system test using the blackbox method on buttons, menus, and various inputs to the system showed that all system processes run as they should or 100% run normally.